2021
DOI: 10.1155/2021/5935170
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Alberta Stroke Program Early CT Score (ASPECTS) in the Outcome of the Acute Ischemic Stroke and Its Correlation with Stroke Subtypes, NIHSS, and Cognitive Impairment

Abstract: Objectives. This study is aimed at correlating ASPECTS with mortality and morbidity in patients with acute middle cerebral artery territory infarction and at determining the cutoff value of ASPECTS that may predict the outcome. Methods. 150 patients diagnosed with acute middle cerebral artery territory infarction were involved in this study. Risk factors, initial NIHSS, and GCS were determined. An initial or follow-up noncontrast CT brain was done and assessed by ASPECTS. Outcomes were determined by mRS during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
1
14
2
4
Order By: Relevance
“…The 6 studies, comprising 735 patients, included in the meta-analysis demonstrated that there was a significant association of increasing ASPECTS with poor functional outcomes at 90 days (SMD = −1.15; 95% CI −1.77–−0.52; p < 0.0001) ( Figure 3 ) [ 16 , 19 , 22 , 33 , 35 , 38 ]. Moderate to considerable heterogeneity was found between the studies (I 2 = 93.1%, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The 6 studies, comprising 735 patients, included in the meta-analysis demonstrated that there was a significant association of increasing ASPECTS with poor functional outcomes at 90 days (SMD = −1.15; 95% CI −1.77–−0.52; p < 0.0001) ( Figure 3 ) [ 16 , 19 , 22 , 33 , 35 , 38 ]. Moderate to considerable heterogeneity was found between the studies (I 2 = 93.1%, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Stroke [39,40] There are 3 types of strokes: ischemic stroke (when blood flow through the artery to the brain becomes blocked, such as blood clots); hemorrhagic stroke (when an artery in the brain breaks and puts too much pressure on brain cells damaging them, that can be intracerebral hemorrhage or subarachnoid hemorrhage); and transient ischemic attack (when blood flow to the brain is blocked for only a short time-usually no more than 5 minutes). The ischemic stroke corresponds to 87% of strokes.…”
Section: Neurological Disorder Definition/etiology/prevalence Signals and Symptomsmentioning
confidence: 99%
“…There are three types of strokes: i) ischemic stroke, referring to a block of blood flow through the artery to the brain, such as blood clots; ii) hemorrhagic stroke, characterizing a damage of the artery in the brain and pressure on brain cells, favoring the intracerebral hemorrhage or the subarachnoid hemorrhage; and iii) transient ischemic attack, that occurs when blood flow to the brain is blocked for only a short time (usually no more than 5 minutes) [31].…”
Section: Whole-body Vibration Exercise In Stroke Individualsmentioning
confidence: 99%